One-pot multicomponent synthesis of highly functionalized bio-active pyrano[2, 3-c]pyrazole and benzylpyrazolyl coumarin derivatives using ZrO2 nanoparticles as a reusable catalyst1. Issue 5 (12th May 2015) - Saha, Arijit; Payra, Soumen; Banerjee, Subhash
<x xml:space="preserve">Abstract</x> Herein, a facile one-pot multicomponent protocol for the synthesis of biologically important pyrano[2, 3-c]pyrazole and benzylpyrazolyl coumarin derivatives has been demonstrated using ZrO2 nanoparticles as reusable catalyst at room temperature.